Myofascial Release for the Treatment of Tension-Type, Cervicogenic Headache or Migraine: A Systematic Review and Meta-Analysis - Zhoupeng Lu; Hui Zou; Peng Zhao; Jialin Wang; Ruirui Wang (Pain Research and Management)
Objective. To assess the effectiveness of myofascial release (MFR) techniques on the intensity of headache pain and associated disability in patients with tension-type headache (TTH), cervicogenic headache (CGH), or migraine. Design. A systematic review and meta-analysis. Methods. Eight databases were searched on September 15, 2023, including PubMed, Scopus, Web of Science, CINAHL, Cochrane Library, Embase, CNKI, and Wanfang Database. The risk of bias was evaluated utilizing the Cochrane Risk of Bias 2 (RoB 2) tool. Results. Pooled results showed that MFR intervention significantly reduces pain intensity [SMD = −2.01, 95% CI (−2.98, −1.03), I2 = 90%, P<0.001] and improves disability [SMD = −1.3, 95% CI (−1.82, −0.79), I2 = 74%, P<0.001]. Subgroup analysis based on the type of headache revealed significant reductions in pain intensity for CGH [SMD = −2.01, 95% CI (−2.73, −1.29), I2 = 63%, P<0.001], TTH [SMD = −0.86, 95% CI (−1.52, −0.20), I2 = 50%, P=0.01] and migraine [SMD = −6.52, 95% CI (−8.15, −4.89), P<0.001] and in disability for CGH [SMD = −1.45, 95% CI (−2.07, −0.83), I2 = 0%, P<0.001]; TTH [SMD = −0.98, 95% CI (−1.32, −0.65), I2 = 0%, P<0.001] but not migraine [SMD = −2.44, 95% CI (−6.04, 1.16), I2 = 97%, P=0.18]. Conclusion. The meta-analysis results indicate that MFR intervention can significantly alleviate pain and disability in TTH and CGH. For migraine, however, the results were inconsistent, and there was only moderate quality evidence of disability improvement for TTH and CGH. In contrast, the quality of other evidence was low or very low.